Prescribing under pressure : parent-physician conversations and antibiotics - Stivers, Tanya (Oxford studies in sociolinguistics., 2007)
Antibiotics will soon no longer be able to cure common illnesses such as strep throat, sinusitis and middle ear infections as they have done for the last 60 years. Antibiotic-resistant bacteria are increasing at a much faster rate than new antibiotics to treat them are being developed. The prescription of antibiotics for viral illnesses is a key cause of increasing bacterial resistance. Despite this fact, many children continue to receive antibiotics unnecessarily for the treatment of viral upper respiratory tract infections. Why do American physicians continue to prescribe inappropriately giv.